Survival/success of dental implants with acid - Etched surfaces : A retrospective evaluation after 8 to 10 years - Nicoli, Lélis Gustavo [UNESP]; de Oliveira, Guilherme José Pimentel Lopes [UNESP]; Lopes, Beatriz Maria Valério [UNESP]; Marcantonio, Cláudio; Zandim-Barcelos, Daniela Leal [UNESP]; Marcantonio, Elcio [UNESP] (FapUNIFESP (SciELO), 2017)
The aim of this study was to conduct a retrospective evaluation of the survival and success rates of dental implants with acid-etched surfaces after 8-10 years of function. Forty-four patients who received 183 implants 8-10 years ago were evaluated. Clinical examinations were performed around the implants and natural teeth. The following parameters were measured: visible plaque index (VPI), marginal bleeding index (MBI), probing depth (PD), bleeding on probing (BOP) and clinical attachment level (CAL). To considerer an implant as a success case, the following criteria were considered: absence of peri-implant infection and suppuration, absence of implant mobility, absence of persistent pain and dysesthesia and absence of radiolucency around the implant. Overall, 178 implants were categorized as surviving (97.3%), 155 were categorized as successful (84.7%), 5 implants (2.7%) were lost (1 in the maxilla and 4 in the mandible), and 3 implants were not under functional load (2.0 %). 20 implants were diagnosed with peri-implantitis. Thus, the survival rate was 97% and the success rate was 85%. In conclusion, implants with acid-etched surfaces showed high survival and success rates after a period of 8 to 10 years of function.
Keywords: Osseointegration; Prostheses and implants; Survival rate